PERUMUSAN KEBIJAKAN PENDIDIKAN YANG BERPERSPEKTIF GENDER DI PROVINSI LAMPUNG (EDUCATION POLICY FORMULATION OF GENDER PERSPECTIVE IN LAMPUNG PROVINCE) - Novita Tresiana (Pusjar SKPP Lembaga Administrasi Negara, 2015)
It talks about the urgency of a gender perspective ineducation policies by integrating a gender perspective into all policies or programs designed Lampung Provincial Education Office. The method used is the evaluation (qualitative). Focus studied is the policy formulation process, understanding,actors, gender management authority lies in the education department, while using descriptive qualitative analysis techniques with interactive analysis. This paper reveals that in the process of formulating education department shows failed to integrate a gender perspective in policy formulation or educational programs. Model formulation dominated incremental models, promoting the consideration of administrative/political. A contributing factor, the lack of understanding of actors, where the authorities are not in a functional structure, so that gender is an exclusive program, not integrated in all programs.Keywords: Gender Perspectives; Policy FormulationTulisan menggagas urgensi kebijakan pendidikan berperspektif gender, melalui integrasi perspektif gender dalam setiap kebijakan/program yang dibuat Dinas Pendidikan Propinsi Lampung. Metode yang digunakan adalah evaluasi (kualitatif), Fokus yang dikaji adalah, proses perumusan kebijakan, pemahaman aktor, letak otoritas pengelolaan gender pada dinas pendidikan. Tehnik analisis digunakan deskriptif kualitatif dengan analisis interaktif. Tulisan ini mengungkap, dinas pendidikan dalam perumusan, gagal mengintegrasikan perspektif gender dalam kebijakan/program pendidikan yang disusunnya. Model perumusan didominasi model inkrementalis, mengedepankan pertimbangan administratif / politis. Faktor penyebabnya, lemahnya pemahaman aktor, letak otoritas tidak berada dalam struktur yang fungsional, sehingga gender menjadi program eksklusif, bukan berintegrasi pada semuaprogram.Kata Kunci : Perspektif Gender, Perumusan Kebijakan